Promoting Equity through Equitable Risk Tradeoffs - Thomas J. Kniesner; W. Kip Viscusi (Institute of Labor Economics (IZA), 2022)
The impact and economic merits of President Biden's Executive Order 13985 on equity depend on how the executive order is implemented. While policy discussion to date has focused on equitable outcomes, we propose framing risk equity policies in terms of equitable risk tradeoff rates based on six policy guidelines. The starting point for ex ante evaluation of equity for mortality risk policies should be the symmetric application of the value of a statistical life (VSL) to all groups. Because of the substantial heterogeneity in VSLs by income and demographic characteristics, symmetric tradeoff rates generate subsidies and deficits relative to private values of risk. Efforts to provide for distributional preferences should be grounded in an understanding of the differentials already provided through application of a uniform VSL. Targeting government programs to specific groups ex ante should be coupled with estimates of the efficiency loss based on symmetric tradeoff rates and the implicit tradeoff rate ratio relative the average VSL needed to support the redistributive policy. Here we propose equity guidance that could be incorporated in a revised version of Office of Management and Budget Circular A-4. We contrast the ex ante equity guidance approach with the ex post risk equity evaluation procedure that is incorporated in the Biden Administration's recently proposed Justice40 plan, where 40 percent of the benefits of existing programs must be targeted to certain minority groups without ex post examination of their cost effectiveness either feasible or currently planned.
Keywords: D61; D63; I18; 330; benefit-cost analysis; Circular A-4; Justice40; risk equity; value of statistical life; regulatory impact analysis